A Prospective Comparative Study on the Clinical Diagnostic Performance of Blood Inflammatory Markers in Acute Appendicitis [Letter] - Peksöz R; Ağırman E; Atamanalp SS (Journal of Inflammation Research)
Rıfat Peksöz,1,* Enes Ağırman,2,* Sabri Selçuk Atamanalp1,* 1Department of General Surgery, Atatürk University Research Hospital, Erzurum, Turkey; 2Department of General Surgery, Erzurum City Hospital, Erzurum, Turkey*These authors contributed equally to this workCorrespondence: Rıfat Peksöz, Department of General Surgery, Atatürk University Faculty of Medicine, Erzurum, Turkey, Tel +90 04423447956, Email rifat-peksoz@hotmail.com